(untitled) (Economic and Political Thought, 2013)
Ḡarar is one of the least known and most misunderstood concepts in Islamic Banking and Finance. Both Islamic scholars of the classical period and contemporary researchers attempted to coin its commonly accepted definition. By far no one has managed to succeed, though. The most prevalent translation of ḡarar is ‘risk’. However, I am proving in the article that the translation is inadequate and misleading. Relying on two major sources of law in Islam: Koran and Sunnah of Muhammad as well as classical and contemporary works by Muslim and secular scholars, I discuss the most common definitions of the term and the social and historical context in which the ḡarar ban came into existence. I also attempt to create a broader definition that could help understand the essence of ḡarar and the reasons why it is banned.